Uterine torsion in a full-term pregnant cat. Issue 2 (August 2017) - Kuroda, Kohei; Osaki, Tomohiro; Harada, Kazuki; Yamashita, Masamichi; Murahata, Yusuke; Azuma, Kazuo; Tsuka, Takeshi; Ito, Norihiko; Imagawa, Tomohiro; Okamoto, Yoshiharu
Case summary: A 5-year-old intact female Maine Coon cat presented with a 2 day history of lethargy, anorexia and anaemia. The cat had bred 60 days previously and jumped from a height 3 days earlier, which was followed by a worsening of its condition. Ultrasonography revealed that two fetuses had died and one remained alive. Urgent surgical intervention was deemed necessary, and the cat underwent a blood transfusion and laparotomy. The right uterine horn was dark red in appearance and had rotated 360° in the clockwise direction at its base. Subsequently, an ovariohysterectomy and caesarean section were performed, and the fetus in the left uterine horn initially survived. Although the cat appeared to recover from anaemia and physical injury, the kitten died on postoperative day 1. Relevance and novel information: In cases involving only one twisted uterine horn, the fetuses located in the contralateral horn could potentially survive; however, many such fetuses do not survive, and only a few reports have described fetal survival in a pregnant cat with uterine torsion. In the present case, early surgical intervention and blood transfusion allowed us to save the cat. Our findings demonstrate the life-saving abilities of initial support treatment and early surgical intervention for both the pregnant cat and fetuses in cases of acute abdomen caused by uterine torsion.